Outcomes of Catheter Ablation of Idiopathic Outflow Tract Ventricular Arrhythmias With an R Wave Pattern Break in Lead V2: A Distinct Clinical Entity. (21st March 2017) - HAYASHI, TATSUYA; SANTANGELI, PASQUALE; PATHAK, RAJEEV K.; MUSER, DANIELE; LIANG, JACKSON J.; CASTRO, SIMON A.; GARCIA, FERMIN C.; HUTCHINSON, MATHEW D.; SUPPLE, GREGORY E.; FRANKEL, DAVID S.; RILEY, MICHAEL P.; LIN, DAVID; et al.
Outflow Tract VT With Pattern Break in Lead V2: Introduction: In outflow tract ventricular arrhythmias (OT‐VAs), an abrupt loss of the R wave in lead V2 compared to V1 and V3 (pattern break in V2–PBV2) suggests an origin close to the anterior interventricular sulcus (anatomically opposite to lead V2) and adjacent to proximal coronaries. We studied the outcome of catheter ablation of OT‐VAs with a PBV2. Methods and Results: Of 130 consecutive patients with idiopathic left bundle block morphology OT‐VAs and transition ≤V4, 12 (9%) had PBV2. Outcomes in this group were compared to the remaining 118 patients. Patients with PBV2 were more likely to be younger (41 ± 18 vs. 50 ± 14 years, P = 0.0384) and women (11 [92%] vs. 70 [59%], P = 0.0302). The earliest activation was at the RVOT in seven, left coronary cusp (LCC) in one, anterior interventricular vein (AIV) in two and the epicardium in two. In five (42%) cases (earliest activation in the AIV in two, epicardium in two, and RVOT below the valve level in one), ablation was aborted due to proximity to the left anterior descending (LAD) coronary artery. After 36 ± 17 months and 1.3 ± 0.5 procedures, VAs elimination was achieved in 58% of patients with PBV2 compared to 89% of the reference population (P = 0.0125) with effective site in five of seven at the most anterior and leftward RVOT adjacent to the pulmonic valve (PV). Conclusions: OT‐VAs with PBV2 demonstrate a unique ECG pattern and challenging catheter ablation. Proximity to LAD precludes ablation in about half. Long‐term VA suppression could be achieved in only 58% of cases most commonly when the earliest site is at the anterior and leftward RVOT just under the PV.